2007
DOI: 10.1111/j.1096-3642.2007.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and ecological significance of Lepidaster grayi, the earliest multiradiate starfish

Abstract: Lepidaster grayi Forbes, 1850, from the Much Wenlock Limestone Formation (Silurian: Wenlock) of England, is the earliest species of starfish (Echinodermata: Asteroidea) to deviate from pentaradial symmetry, having 13 rays rather than five. Based on the patterns of supernumerary ray development seen in extant multiradiate asteroids, two possible models are evaluated for the origin of the eight additional rays seen in L. grayi . In the 'all-in-one' model, all rays were added in the same interradius, whereas in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…2000)], and represents a significant development in the evolutionary history of starfish. The origin and ecological implications of this are discussed elsewhere (Herringshaw et al . in press), but recent studies on modern multiradiate asteroids (e.g.…”
mentioning
confidence: 86%
“…2000)], and represents a significant development in the evolutionary history of starfish. The origin and ecological implications of this are discussed elsewhere (Herringshaw et al . in press), but recent studies on modern multiradiate asteroids (e.g.…”
mentioning
confidence: 86%
“…These authors noted that the maximum number of arms in recent species in which arm number is fixed is about 11. Herringshaw et al (2007) reported 13 arms as typical of the Silurian species Lepidaster grayi Forbes, 1850, whereas most specimens of Helianthaster in which arm number can be determined have 16 arms; Lehmann (1957) makes special note of the smallest specimen available to him, with an arm length of only 13 mm; this specimen, illustrated by Lehmann, has only 15 arms. This author also illustrated a specimen of arm length of 35 mm with 16 arms; and FMNH PE 56571, arm length about 16 mm beyond the disk, also has 16 arms (Fig.…”
Section: The Multiarmed Conditionmentioning
confidence: 94%
“…Ambulacrals are bordered by dorsal surfaces of adambulacrals pushed through surface during compaction. Scale bars = 2 mm b Re-evaluation of the Devonian family Helianthasteridae Gregory, 1899 301 Hotchkiss (2000) argued that the multiarmed condition was derived from the five-armed, and Herringshaw et al (2007) recognized two modes of addition, one in which supernummary arms are added in all interarm areas except that with the madreporite (the authors' ''quadrants'' pattern), and a second in which arms are only added in a single interarea (the authors' ''all-in-one'' pattern). Tools used to recognize pattern include position of the madreporite and anus, and arm number (because arms are added in recognizable series in the quadrant pattern).…”
Section: The Multiarmed Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unfortunate that this type of predation leaves no diagnostic trace fossils; this factor, combined with the poor body fossil record of asteroids, makes it difficult to assess the importance of extra-oral feeding over geological time. There is disagreement over when the ability to feed in this way evolved because of different interpretations of the limited body fossils (see hErringshaw, sMith, & thoMas, 2007); however, exceptional preservation may provide evidence of starfish caught in the act of feeding in this manner on an Ordovician bivalve (blaKE & guEnsbErg, 1994). Despite this evidence, it may be that extra-oral feeding in asteroids did not become widespread until the Jurassic radiation of forcipulate-solasteroid starfish in the Jurassic (blaKE, 1993).…”
Section: Prising Apart Valvesmentioning
confidence: 99%